A multi-stimuli-responsive fluorescence switch based on E–Z isomerization of hydrazone. Issue 47 (25th April 2016) - Zheng, Hai-Rong; Niu, Li-Ya; Chen, Yu-Zhe; Wu, Li-Zhu; Tung, Chen-Ho; Yang, Qing-Zheng
Abstract : We report a new strategy to construct fluorescence switches by taking advantage of the E – Z isomerization of the hydrazone group. Abstract : We report a new strategy to construct fluorescence switches by taking advantage of the E – Z isomerization of the hydrazone group. The switch, synthesized by linking pyridyl-2-aldehydehydrazone to a BODIPY fluorophore, was able to exist in three forms: E -BODIPY, Z -BODIPY andprotonated BODIPY with different photophysical properties. Reversible ON/OFF fluorescence switching among them was realized by multiple stimuli such as irradiation and addition of acid/base.